Identifying Protective Factors That Mitigate Relations Between Experiences with Violence and Gun Carriage for Black Young Adults Living in Economically Marginalized Urban Communities - Walsh, Colleen S. (Journal of interpersonal violence, 2023)
Gun violence disproportionately impacts Black young adults living in economically marginalized urban communities and results in increased risk for injury and death. This study identifies protective factors across the ecological model for Black young adults experiencing peer-based physical and relational aggression and victimization that can mitigate the likelihood of gun carriage. The sample included 141 Black young adults living in economically marginalized communities who had experienced violence. Regression and moderation analyses indicated (1) peer-based physical and relational aggression and victimization negatively associated with gun carriage, and (2) personal assets, positive outlook, student status, and neighborhood attachment interacted with peer-based violent experiences and had protective associations with gun carriage. Findings from this study indicate a need for tailored prevention, policy efforts in order to support Black young adults and decrease gun carriage.